Negative reviews, positive impact: Consumer empathetic responding to unfair word of mouth - ALLARD, Thomas (Institutional Knowledge at Singapore Management University, 2020)
This research documents how negative reviews, when perceived as unfair, can activate feelings of empathy toward firms that have been wronged. Six studies and four supplemental experiments provide converging evidence that this experienced empathy for the firm motivates supportive consumer responses such as paying higher purchase prices and reporting increased patronage intentions. Importantly, this research highlights factors that can increase or decrease empathy toward a firm. For instance, adopting the reviewer's perspective when evaluating an unfair negative review can reduce positive consumer responses to a firm, whereas conditions that enhance the ability to experience empathy-such as when reviews are highly unfair, when the identity of the employee is made salient, or when the firm responds in an empathetic manner-can result in positive consumer responses toward the firm. Overall, this work extends the understanding of consumers' responses to word of mouth in the marketplace by highlighting the role of perceived (un)fairness. The authors discuss the theoretical and practical implications of the findings for better management of consumer reviews.